Covid-19 crisis in Romania - between perception and attitude - Rus, Mihaela; Sandu, Mihaela Luminita; Tasențe, Tănase (Technium Social Sciences Journal, 2020)
The 2019–2020 coronavirus pandemic, also known as Covid-19, debuted on December 12, 2019 in downtown Wuhan, China, when a group of people with pneumonia of unknown cause appeared, was mainly linked by the owners of stalls working on the Huanan fish market, who also sold live animals. The virus presents evidence of person-to-person transmission, and the transmission rate (infection rate) appears to have escalated by mid-January. As measures to prevent the spread of the virus, Romania has adapted a strategy to prevent and control this situation, such as: cancellation or closure of air flights, cancellation of residential meetings, closure of large stores, mandatory self – quarantine of infected persons. Thus, institutions and factories were closed, with the exception of the vital institutions, the closure of churches, educational institutions, universities, sports halls. Awareness campaigns have been launched through the media and social media, the use of disinfectant materials to clean the hands, the use of protective masks and medical gloves, the sanitizing of neighborhoods and roads with cleaning materials. The objective of the study was to determine the effects of the new Coronavirus (COVID19) on the population, both in perception and in attitude. The sample consists of 244 persons and the data obtained after the application of the questionnaire were statistically processed, obtaining the following conclusions: most of the respondents consider that the information received about Covid-19 is correct, a smaller percentage believe that the news about the new Coronavirus are exaggerated; At the same time, the respondents affirm that they will respect all the measures that the Government imposes on them: they will stay at home, they will go out only to buy the necessary products, they will wear masks, gloves, they will wash their hands often. Moreover, most respondents believe that both the country's economy and their personal economy will have to suffer greatly during this period of crisis.